The influence of roller compaction processing variables on the rheological properties of granules - Tim Freeman; Harmut Vom Bey; Michael Hanish; Katrina Brockbank; Brian Armstrong (Elsevier, 2016)
This study is part of an ongoing project to enable the full specification of the Design Space for roller compactor systems and shows how the processing parameters influence the behaviour of the product granulate from a placebo formulation. Granulate was produced using a proprietary roller compactor by varying the compaction pressure and gap width, and the dynamic, bulk and shear properties of the resultant granulates were measured. The results demonstrate several rheological properties of the granulate, which have been shown to be closely correlated with variance in die filling and tablet strength, and are predictably influenced by the processing parameters.